Comparison of sociodemographic factors, lifestyle, and gastrointestinal symptoms between patients with endometriosis and IBS - Petersson, Agnes ; 0000-0003-0224-5311; Roth, Bodil; Jokubkiene, Ligita; Sladkevicius, Povilas ; 0000-0001-9563-8135; Ohlsson, Bodil (BMC Gastroenterology, 2025)
Objectives: Endometriosis and Irritable bowel syndrome (IBS) are two common diseases with overlapping symptomatology, causing confusion and delay in the diagnostic process. The objective of this study was to identify differences between endometriosis and IBS diagnosed according to Rome IV, by comparing sociodemographic factors, lifestyle habits, and gastrointestinal symptoms. Materials and methods: Patients with endometriosis (n = 214), confirmed by laparoscopy or at transvaginal ultrasound, were recruited at the Department of Gynecology, Skåne University Hospital, Malmö. Patients with IBS (n = 199) were recruited from primary care centers, the Department of Gastroenterology, Skåne University Hospital, Malmö, and by advertisements at social media. All study participants answered questionnaires regarding sociodemographic factors, lifestyle habits, and medical history. Gastrointestinal symptoms were evaluated using the validated Visual Analog Scale for Irritable Bowel Syndrome (VAS-IBS). Results: There were limited differences in sociodemographic factors and lifestyle habits between women with endometriosis and IBS. However, endometriosis patients mainly needed analgetic treatment, opioids in 9.3% of cases, whereas IBS patients often needed drugs for intestinal dysfunction. GI symptoms were more aggravated in IBS than in endometriosis, especially diarrhea and constipation. The initial trigger events differed between the two diseases: menarche being most common in endometriosis and stress or infection/antibiotic treatment being most common in IBS. Both groups reported improvement of GI symptoms after dietary changes. Conclusions: The findings indicate that a thorough anamnesis about onset of disease and medication needs together with rating of gastrointestinal symptoms by validated instruments could be useful tools to differentiate between endometriosis and IBS in clinical practice.
Keywords: Endometriosis; Gastrointestinal symptoms; IBS; Lifestyle habits; Sociodemographic factors; Trigger events